Rituximab used for simultaneous treatment of PR3‐ANCA positive vasculitis associated with rheumatoid arthritis: A case report. Issue 12 (26th August 2020) - Yamada, Akihiro; Sogabe, Ayuko; Okuda, Yasuaki
Abstract: We treated PR3‐ANCA positive vasculitis in a patient diagnosed with rheumatoid arthritis using rituximab. Monoclonal antibody therapy can be used to simultaneous treat more than one collagen disease in such patients. This suggests that shared pathogenic pathways exist between different collagen diseases. Abstract : We treated PR3‐ANCA positive vasculitis in a patient diagnosed with rheumatoid arthritis using rituximab. Monoclonal antibody therapy can be used to simultaneous treat more than one collagen disease in such patients. This suggests that shared pathogenic pathways exist between different collagen diseases.